Comparative characterization of inflammatory profile and oral microbiome according to an inflammation-based risk score in ST-segment elevation myocardial infarction - Hernández-Ruiz, Paulina; Amezcua-Guerra, Luis M.; López-Vidal, Yolanda; González-Pacheco, Héctor; Pinto-Cardoso, Sandra; Amedei, Amedeo; Aguirre-García, María Magdalena (Frontiers in Cellular and Infection Microbiology, 2023)
Ischemic heart disease considers the myocardial infarction (MI), either non-ST-segment elevation (non-STEMI) or ST-segment elevation myocardial infarction (STEMI); this represents the main cause of mortality in Mexican population. Regarding to the inflammatory state, this is reported to be a major prognostic factor of mortality for patients with MI. One of the conditions capable of producing systemic inflammation is periodontal disease. It has been proposed that the oral microbiota is translocated through the bloodstream to the liver and intestine, generating intestinal dysbiosis. The aim of this protocol is to assess oral microbiota diversity and circulating inflammatory profile in STEMI patients stratified according to an inflammation-based risk scoring system. We found that Bacteriodetes phylum was the most abundant in STEMI patients, and Prevotella was the most abundant genus, with a higher proportion in periodontitis patients. In fact, Prevotella genus was found to correlate positively and significantly with elevated IL-6 concentration. Our study defined a non-causal association inferred between the cardiovascular risk of STEMI patients, determined by changes in the oral microbiota that influence the development of periodontal disease and its relationship with the exacerbation of the systemic inflammatory response.